Response of Maize Grown on Overburden Soil in a Coal Mining Area without Top Soil to Various Compost Sources - Purnomo, Erry (JOURNAL OF TROPICAL SOILS, 2015)
Soil in Kalimantan Island is considered infertile. To obtain a reasonable crop yield a high input fertilizer package should be applied. The situation will be worsening when an open pit system of coal mining adopted. Failure in re-arranging the soil layers can result in decreasing soil fertility compared to original soil prior to mining. This study aimed to determine the improvement of soil fertility of a disposal without top soil by using composts from various sources, namely, the public garbage pile, commercial compost, and compost from kitchen waste. The experiment was conducted in a disposal area of a coal mining of PT AI. A series of application rate of compost was set. This was 0, 5, 10, and 20 tonne compost ha-1. A plot with top soil was involved for another control. Maize was selected as the plant indicator to evaluate the effect of treatments applied. It can be concluded that application of composts to reclamation area without top soil significantly improve soil fertility. Among the composts used, K-compost (compost from kitchen waste) was the best in improving soil fertility. There were some characters of the compost that had not enough to support maize yield. These were P, K, and pH. Addition of P and K fertilizers and lime material are needed. Of the equation coefficients obtained, the b coefficient of equation belong to K-compost was higher than of the others.